2019
DOI: 10.13057/biodiv/d200432
|View full text |Cite
|
Sign up to set email alerts
|

A novel Bacillus sp. isolated from rotten seaweed: Identification and characterization alginate lyase its produced

Abstract: Abstract. Zilda DS, Yulianti Y, Sholihah RF, Subaryono S, Fawzya YN, Irianto HE.2019. A novel Bacillus sp. isolated from rotten seaweed: identification and characterization alginate lyase it is produced. Biodiversitas 20: 1166-1172. Alginate lyase has been known as potential biocatalyst not only for industrial but also medicinal application especially for the production of oligosaccharides which have distinct bioactivities. An alginate lyase, AlgT513, has been isolated from rotten seaweed bacterium strain T513… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The colonies growing on solid MS were isolated and purified. The ability of the bacterial isolates to degrade polysaccharides was assessed by a 24-h incubation and subsequent staining with Lugol’s iodine solution, followed by staining with CaCl 2 solution (10%) with 1-h incubation to observe the capability of degrading alginate [ 70 ]. The most potential bacterial isolate was subsequently tested for the antimicrobial ability of its extracellular fraction against Staphylococcus aureus ATCC®25923™, an opportunistic bacterial pathogen that can cause various infections and food poisoning [ 14 , 63 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colonies growing on solid MS were isolated and purified. The ability of the bacterial isolates to degrade polysaccharides was assessed by a 24-h incubation and subsequent staining with Lugol’s iodine solution, followed by staining with CaCl 2 solution (10%) with 1-h incubation to observe the capability of degrading alginate [ 70 ]. The most potential bacterial isolate was subsequently tested for the antimicrobial ability of its extracellular fraction against Staphylococcus aureus ATCC®25923™, an opportunistic bacterial pathogen that can cause various infections and food poisoning [ 14 , 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…In search for biotechnologically potential genes from seaweed epibionts, we initially isolated a novel polysaccharide-degrading bacterial species associated with the Indonesian brown algae Hydroclathrus sp. [ 70 ]. We found that the cell-free culture of this epibiont was able to inhibit the bacterial pathogen S. aureus , indicating its potential ability to produce antimicrobial substance extracellularly.…”
Section: Introductionmentioning
confidence: 99%
“…[ 84 ], Defluviitalea phaphyphila [ 85 ], Klebsiella aerogenes type 25 [ 86 ], Pseudomonas alginovora XO17 [ 87 ], Bacillus sp. [ 42 , 88 ], Corynebacterium sp. ALY-1 [ 89 ], Zobellia galactanivorans [ 90 ], and Agarivorans sp.…”
Section: Marine Sources Of Alginate Lyasementioning
confidence: 99%
“…A couple of alginate lyases were separated from different kinds of microorganisms in the past several years, especially from the bacteria on brown algae (such as Bacillus sp. obtained from rotten seaweed) [ 88 ], Paenibacillus algicola isolated from rotten brown algae samples collected from China [ 92 ], and Pseudoalteromonas sp. SM0524 separated from marine kelp residues [ 93 ].…”
Section: Alginate Lyase-producing Marine Bacteriamentioning
confidence: 99%
“…Bacillus genera are recognized for the making of wide range of medicinal, agricultural, pharmaceutical and industrial products, example.g., Bacillus tequilensis as alginate lyase producer (Zilda et al 2019), Bacillus subtilis MA9 produce thermostable α-amylase enzyme (Devi et al 2010), Bacillus cereus KKT 1, B. cereus KKT 14, B. cereus KKT 19. Bacillus thuringiensis KKT 6, produce chitin-degrading enzyme (Puspita et al 2017) and B. cereus, B. subtilis B. thuringiensis, and B. pumilus as antibiotic-producing agent (Amin et al 2015;Magda and Hamed 2016).…”
Section: Phylogenetic Studymentioning
confidence: 99%